Existence of Lagrange multipliers for set optimization with application to vector equilibrium problems. (4th May 2022) - Amahroq, Tijani; Oussarhan, Abdessamad
ABSTRACT: In this paper, we prove some results concerning the existence of the Lagrange multipliers for set optimization problems. Moreover, we indicate how these results may be applied to provide some optimality conditions for weak vector equilibrium problems.